2021
DOI: 10.1002/smtd.202001108
|View full text |Cite
|
Sign up to set email alerts
|

Ultraefficiently Calming Cytokine Storm Using Ti3C2Tx MXene

Abstract: During the global outbreak of COVID‐19 pandemic, “cytokine storm” conditions are regarded as the fatal step resulting in most mortality. Hemoperfusion is widely used to remove cytokines from the blood of severely ill patients to prevent uncontrolled inflammation induced by a cytokine storm. This article discoveres, for the first time, that 2D Ti3C2Tx MXene sheet demonstrates an ultrahigh removal capability for typical cytokine interleukin‐6. In particular, MXene shows a 13.4 times higher removal efficiency ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Among of many methods of hydrogen production, the developments of sustainable and clean route, involving electrocatalytic water splitting, are urgent . However, the challenges of hydrogen evolution reaction (HER) rely on design and synthesis of outstanding electrocatalysts . Although Pt‐based catalysts are confirmed to be high active electrocatalyst for HER, Pt‐free materials including transition metal carbides, sulfides, and oxide materials are expected to substitute for noble metal as electrocatalysts for water splitting because of their low cost and high abundance in nature.…”
Section: Methodsmentioning
confidence: 99%
“…Among of many methods of hydrogen production, the developments of sustainable and clean route, involving electrocatalytic water splitting, are urgent . However, the challenges of hydrogen evolution reaction (HER) rely on design and synthesis of outstanding electrocatalysts . Although Pt‐based catalysts are confirmed to be high active electrocatalyst for HER, Pt‐free materials including transition metal carbides, sulfides, and oxide materials are expected to substitute for noble metal as electrocatalysts for water splitting because of their low cost and high abundance in nature.…”
Section: Methodsmentioning
confidence: 99%
“…The results of previous work showed that the clearance of electrolytes and beneficial proteins in plasma by MXene was within the allowable range. The effect on coagulation time and hemolysis rate was also in the normal range, which proved that MXene had good biocompatibility [24] …”
Section: Resultsmentioning
confidence: 74%
“…The effect on coagulation time and hemolysis rate was also in the normal range, which proved that MXene had good biocompatibility. [24] To explore the adsorption capacity of MXene for bilirubin, we carried out the adsorption experiment of MXene in the bilirubin solution. According to the previous data, the normal reference range of adult total bilirubin is about 1.7-20.1 μmol L À 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, there are more and more fundamental researches on the application of electrocatalysis [14–17] . Up to date, Pt−based catalysts and RuO 2 /IrO 2 with low overpotentials and high durability are state−of−the−art HER and OER electrocatalysts, respectively [18,19] . However, since they belong to precious metal−based materials, they suffer from their high cost and scarcity.…”
Section: Introductionmentioning
confidence: 99%